2002
DOI: 10.1007/s00264-001-0316-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two total knee prostheses on the incidence of patella clunk syndrome

Abstract: The patella clunk syndrome is not an uncommon complication, particularly after posterior-stabilized (PS) total knee arthroplasty. The present study was a consecutive unselected series comparing the incidence of the patella clunk syndrome amongst two comparable groups of elderly patients with knee arthritis implanted with the Insall-Burstein (IB II) total knee system and the newer NexGen Legacy total knee prosthesis. While 7.5% of patients in the PS IB II group developed patella clunk syndrome, none occurred in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
41
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 9 publications
0
41
1
Order By: Relevance
“…In either case, the altered patellofemoral kinematics may be in part responsible for the development of patellar clunk syndrome. 2 The effect of increased knee flexion achieved with the MIS approach, which resulted in an increase in patella clunk, Patellar crepitus and clunk syndrome have also been attributed to abnormal patellar tracking secondary to inadequate soft-tissue balance or tibial component malrotation and mal tracking of the patella. 12 In patients with/without pre-op PF pain, the incidence of postop PF pain, clunk and crepitus is lower in patients who underwent patelloplasty.…”
Section: Etiopathogenesismentioning
confidence: 99%
See 4 more Smart Citations
“…In either case, the altered patellofemoral kinematics may be in part responsible for the development of patellar clunk syndrome. 2 The effect of increased knee flexion achieved with the MIS approach, which resulted in an increase in patella clunk, Patellar crepitus and clunk syndrome have also been attributed to abnormal patellar tracking secondary to inadequate soft-tissue balance or tibial component malrotation and mal tracking of the patella. 12 In patients with/without pre-op PF pain, the incidence of postop PF pain, clunk and crepitus is lower in patients who underwent patelloplasty.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…It is concluded that both the height and the width of the intercondylar box were design features leading to synovial entrapment. 2 The incidence of patellofemoral complications in patients with PS TKAs has long been attributed to patellar baja and anterior placement of the tibial tray. A lower Insall-Salvati ratio, lower patellar component height, lower position of the proximal pole of the patella, and anteriorization of the tibial tray were all associated with a higher incidence of patellar clunk syndrome.…”
Section: Etiopathogenesismentioning
confidence: 99%
See 3 more Smart Citations